2015
DOI: 10.1515/msp-2015-0110
|View full text |Cite
|
Sign up to set email alerts
|

A DFT study of the effects of Sc doping on electronic and optical properties of CdS nanoparticles

Abstract: In the present work a systematic study was carried out to understand the influence of Sc doping on electronic and optical properties of CdS nanoparticles. The geometry optimization and symmetry computation for CdS and Sc doped CdS nanoparticles using Density Functional Theory (DFT) on B3LYP level with the QZ4P for Cd and DZ2P for sulphur and Sc were performed by Amsterdam Density Functional (ADF). The results show that HOMO-LUMO gap as well as electronic and optical properties of CdS clusters vary with Sc dopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…To verify the PET process between the N, Si-CDs and BLFX, the LUMO and HOMO energy levels of the BLFX molecule and N, Si-CDs were calculated. [52][53][54] First, for the BLFX molecule, DFT calculations were performed using the Gaussian 09 program based on the B3LYP level. The molecular orbital diagram of DFT is shown in Fig.…”
Section: Response Mechanism For the Detection Of Blfxmentioning
confidence: 99%
“…To verify the PET process between the N, Si-CDs and BLFX, the LUMO and HOMO energy levels of the BLFX molecule and N, Si-CDs were calculated. [52][53][54] First, for the BLFX molecule, DFT calculations were performed using the Gaussian 09 program based on the B3LYP level. The molecular orbital diagram of DFT is shown in Fig.…”
Section: Response Mechanism For the Detection Of Blfxmentioning
confidence: 99%
“…The geometry optimization and symmetry computation for CdS and Sc doped CdS nanoparticles using Density Functional Theory (DFT). The results show that HOMO-LUMO gap as well as electronic and optical properties of CdS clusters vary with Sc doping [20]. It is found that the thickness change of the scandium layer will bring great in uence on a higher transconductance with analysis of the RF performance of novel Sc-Doped GaN high-electron-mobility transistors (HEMTs) [21].…”
Section: Introductionmentioning
confidence: 99%